Sensitivity analysis of leakage of rockfill dam caused by composite geomembrane defect. Issue 1 (July 2021) - Jie, Yang; Guang, Cheng; Pengli, Zhang; Jiaming, Wang
Abstract: To study the influence of different geomembrane defects on the seepage field of a typical concrete inclined wall rockfill dam with a dam height of 85m, the saturated-unsaturated seepage finite element theory is applied to construct a three-dimensional numerical calculation model, and the seepage field of the dam under different geomembrane defects is numerically simulated and analysed. The calculation conditions of geomembrane defect size, head height, defect position, defect number and spacing are worked out respectively, and then the influence law of composite geomembrane breakage on dam seepage under pressure head is analysed. The results of the calculation model show that when the composite geomembrane has a single size defect and different position defect. The leakage caused by defects is relatively small, which has little effect on the overall seepage of the dam; When there are many defects in composite geomembrane, there is a linear relationship between the number of defects and the seepage of the dam body. When the defects are more concentrated, the phenomenon of concentrated seepage may occur, and the seepage of the dam body changes obviously.